(3efXhQ cdjs - (3eGLO YHO GdgGOj(B, (3eSGYOIs ((3YeGf(B:s (3OGQ GdeSjQ ddfTQ hGdJhRjY(B,s, 2015)
(3eONd YGe aj OQGSI GdefXeI, GdJWhQ GdJGQjNj dfXQjI GdefXeI, GdCgOGa hGdZGjGJ GdJfXjejI, GdEOGQI GdESJQGJjLjI hGdJhLg GdESJQGJjLj ddefXeI, EOGQI GdHjFI GdNGQLjI hGdOGNdjI ddefXeI, Gdgjcd GdJfXjej, MLe GdefXeI hYeQgG hOhQI MjGJgG, EOGQI GdJcfhdhLjG aj GdefXeGJ, EOGQI GdeYdheGJ aj GdefXeGJ, EOGQI GdUQGY GdJfXjej, EOGQI KbGaI GdefXeI, EOGQI GdJZjjQ hGdJWhjQ GdJfXjej, EOGQI GdEHOGY GdJfXjej(B.s
Keywords: (3EOGQI GdeDSSGJs; (3EOGQI(B- (3GdefXeIs; (3GdefXeGJs